QS al-Ma’un sebagai Teks Emansipatoris: Kritik terhadap Simbolisme Keberagamaan Digital melalui Hermeneutika Pembebasan Hasan Hanafi: QS al-Ma'un as an Emancipatory Text: A Critique of Digital Religious Symbolism through Hasan Hanafi's Hermeneutics of Liberation - Aswar, Aswar; Shorfana, M. Rizky; Nadia, Nadia (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This study explores QS al-Ma’un (107:1-7) through the lens of Hanafi’s liberation hermeneutics to critique the practice of digital religiosity on social media. The background of the study stems from the paradox of worship: while expanding spiritual access, online worship practices are often ritualistic, symbolic, and lack a strong dimension of social solidarity. This research employs a qualitative, descriptive-analytical method, applying Hanafi’s three levels of hermeneutics: historical (the socio-historical context of QS al-Ma’un’s revelation), eidetic (the universal meaning), and practical (its application to digital phenomena). The findings indicate that the values of al-Ma’un, which condemn prayer performed without concern for the poor and orphans, are highly relevant in critiquing “digital ritualization” (e.g., exhibitionist content, automated charity, and similar acts) that tends to focus on self-image and algorithms rather than genuine social transformation. The study also acknowledges the positive potential of digital spaces as platforms for disseminating inclusive religious values, provided they are guided by critical awareness. This research contributes to the extension of liberation hermeneutics' applicability to digital religiosity, offering a new evaluative framework for contemporary worship practices based on principles of justice, empathy, and social commitment. The study’s implications underscore the need to reconstruct digital worship practices as expressions of concrete solidarity, aiming to foster a liberatory form of religiosity in the digital age.